Do Prolonged Prophylactic Antibiotics Reduce the Incidence of Surgical-Site Infections in Immediate Prosthetic Breast Reconstruction?. Issue 6 (December 2016) - Wang, Frederick; Chin, Robin; Piper, Merisa; Esserman, Laura; Sbitany, Hani
Abstract : Background: Approximately 50, 000 women in the United States undergo mastectomy and immediate prosthetic breast reconstruction annually, and most receive postoperative prophylactic antibiotics. The effect of these antibiotics on the risk of surgical-site infections remains unclear. Methods: The authors searched the Medline, Embase, and Cochrane Library databases for studies that compared less than 24 hours and greater than 24 hours of antibiotics following immediate prosthetic breast reconstruction. Primary outcomes were surgical-site infections and implant loss. Conservative random effects models were used to obtain pooled relative risk estimates. Results: The authors identified 927 studies, but only four cohort studies and one randomized controlled trial met their inclusion criteria. Unadjusted incidences of surgical-site infections were 14 percent with more than 24 hours of antibiotics, 19 percent with less than 24 hours of antibiotics, and 16 percent overall. Unadjusted incidences of implant loss were 8 percent with more than 24 hours of antibiotics, 10 percent with less than 24 hours of antibiotics, and 9 percent overall. The pooled relative risk of implant loss was 1.17 (95 percent CI, 0.39 to 3.6) with less than 24 hours of antibiotics, which was not statistically significant. Conclusions: Prolonged antibiotic use did not have a statistically significant effect on reducing surgical-site infections or implant loss. There was significant heterogeneity between studies, and prolonged antibiotics may have increased the risk of implant loss in the randomized controlled trial. Definitive evidence may only be obtained with data from more prospective randomized controlled trials. Abstract : This and Related "Classic" Articles Appear on Prsjournal.Com for Journal Club Discussions.